Strong Solution of the Obstacle Problem for Fully Nonlinear Elliptic Equations (Journal of Partial Differential Equations, 1991)
In this paper we obtain the existence of W^{2, &#8734} solutions of the obstacle problems for fully nonlinear elliptic equations under more general structure conditions than those in [1] by using the mollifier approach, which is also extended in our discussion.
Keywords: Strong solution; fully nonlinear elliptic equations; the mollifier approach